Volunteerism and corporate social responsibility in Ukrainian companies during war - Yarmak, Kateryna (Запоріжжя: ТДАТУ, 2026)
Since the start of the ongoing large-scale war in 2022, both volunteerism and corporate social responsibility (CSR) in Ukraine have changed dramatically. As a result of military threats, economic instability, and mass displacement, businesses have adopted a much wider-ranging social responsibility than before. CSR has transcended its traditional reputation/ethical rationale and now constitutes part of organisational resilience and national support. Ukrainian businesses have shown their willingness to provide humanitarian assistance and support to the armed forces, as well as engage in volunteer activities, thereby aligning business activities with community needs.
Keywords: volunteerism; corporate social responsibility